(untitled) (EAAE Annual Conference Proceedings, 2023)
The Thesis Seminar “Theory and Critic of Architectural Action” is a multidisciplinary didactic experience designated to study the methodological aspects related to developing a research project in architectural history and/or design, and notably aimed at developing Master’s Degree Graduation. The Seminar identifies six key nodes in research on project practice and takes a multidisciplinary view to tackle them critically.